Serial Min-max Decoding Algorithm Based on Variable Weighting for Nonbinary LDPC Codes - Zhongxun Wang; Xinglong Gao; Tiancheng Chen (Institute of Advanced Engineering and Science, 2014)
In this paper, we perform an analysis on the min-max decoding algorithm for nonbinary LDPC(low-density parity-check) codes and propose serial min-max decoding algorithm. Combining with the weighted processing of the variable node message, we propose serial min-max decoding algorithm based on variable weighting for nonbinary LDPC codes in the end. The simulation indicates that when the bit error rate is 10^-3,compared with serial min-max decoding algorithm ,traditional min-max decoding algorithm and traditional minsum algorithm ,serial min-max decoding algorithm based on variable weighting can offer additional coding gain 0.2dB、0.8dB and 1.4dB respectively in additional white Gaussian noise channel and under binary phase shift keying modulation. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4176